2005
DOI: 10.1039/b506199g
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric pitch length tuning of a dinuclear double helicate

Abstract: Self assembly of the ditopic ligand L1 with Cu2+ gives the dinuclear double helicate [Cu2(L1)2]4+, which can further coordinate s-block cations. This coordination alters the helicate pitch to a variety of different lengths depending on the size and charge of the guest cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…We have previously observed similar trends in a series of dicopper(II) doublestranded helicates, whose solid-state internuclear separations were found to depend on the size and charge of an s-block cation located in a remote crown ether binding site. [4] This disparity invokes the influences of other factors, arguably the most apparent of which is the accumulation of charge in the s-block cation bound complexes, that is, both helicate disassembly and pitch increase could be the result of electrostatic repulsion effects. Placing two crown etherbound Ba 2 + ions in close proximity to the dicopper(I) helicate core increases electrostatic repulsion within the complex and encourages the N-donor bound Cu I ions to move further apart.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously observed similar trends in a series of dicopper(II) doublestranded helicates, whose solid-state internuclear separations were found to depend on the size and charge of an s-block cation located in a remote crown ether binding site. [4] This disparity invokes the influences of other factors, arguably the most apparent of which is the accumulation of charge in the s-block cation bound complexes, that is, both helicate disassembly and pitch increase could be the result of electrostatic repulsion effects. Placing two crown etherbound Ba 2 + ions in close proximity to the dicopper(I) helicate core increases electrostatic repulsion within the complex and encourages the N-donor bound Cu I ions to move further apart.…”
Section: Discussionmentioning
confidence: 99%
“…s Block cation binding studies 4 ] 2 and L 1 was recorded before and after treatment with one equivalent of BaA C H T U N G T R E N N U N G (ClO 4 ) 2 ( Figure 3). Comparison of the spectra shows that whilst the aromatic region remains largely unaffected, the methylene protons (4.6 < d < 5.4) experience a significant change in both chemical shift and dynamic behaviour following addition of Ba 2 + ions; the initial singlet resonance being resolved into two doublets, both of which are shifted downfield by up to 0.4 ppm.…”
Section: Complex Of L 1 With Copper(i)mentioning
confidence: 99%
See 2 more Smart Citations
“…The results reveal limitations to the use chiral ligands with hydrogen bond donor groups located for intermolecular hydrogen bonding for the selfassembly of helical coordination polymers and include the X-ray crystal structure of an unusual mixed-valent Cu(II) 2 Cu(I) trimer in which CuBr 2À 3 anion acts as a bridging ligand between the two Cu(II) centres.The predictable formation of helical coordination polymers is a contemporary challenge as these materials have applications spanning diverse areas such as asymmetric catalysis, chiral separations and optoelectronics [1][2][3][4][5][6][7][8][9][10][11]. We recently reported that helical copper(II) coordination polymers can be predictably constructed using hydrogen bonding interactions [4].…”
mentioning
confidence: 99%